1976
DOI: 10.1901/jaba.1976.9-1
|View full text |Cite
|
Sign up to set email alerts
|

Training Children With Asthma to Use Inhalation Therapy Equipment1

Abstract: In Experiment I, four children with asthma were taught to use the intermittent positivepressure breathing (IPPB) apparatus, a device that delivers bronchodilator medication to the lungs under positive pressure. Because these youngsters had not learned to use the device with repeated instructions, script with back-up reinforcement was introduced to train sequentially three responses-eye fixation, facial posturing, and diaphragmatic breathing-according to a multiple-baseline design. The procedures were effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Using shaping, modeling, and reinforcement, they taught children with asthma to correctly use the nebulizer during attacks. Renne and Creer (1976) observed that many children with asthma did not use a compressor-driven nebulizer correctly. A behavioral analysis of their children's behavior indicated that they had to coordinate three responsesdiaphragmatic breathing, attending to the apparatus, and inhaling the dispensed medication correctly-in order for the apparatus to achieve this goal.…”
Section: Shapingmentioning
confidence: 99%
“…Using shaping, modeling, and reinforcement, they taught children with asthma to correctly use the nebulizer during attacks. Renne and Creer (1976) observed that many children with asthma did not use a compressor-driven nebulizer correctly. A behavioral analysis of their children's behavior indicated that they had to coordinate three responsesdiaphragmatic breathing, attending to the apparatus, and inhaling the dispensed medication correctly-in order for the apparatus to achieve this goal.…”
Section: Shapingmentioning
confidence: 99%
“…For this reason, it is important to teach children to comply with lens insertion and removal. Shaping, the differential reinforcement of successive approximations to an end goal (Catania, 1984), has been used successfully to teach a variety of skills, induding conversation skills (Bourgeois, 1990), glasses use (Wolf, Risley, & Mees, 1964), inhalation therapy responses (Renne & Creer, 1976), and compliance with radiation therapy (Mathews & Grantmyre, 1985). The purpose of this study was to document and evaluate systematically the effectiveness of a shaping procedure to teach contact lens use in young children.…”
mentioning
confidence: 99%
“…Studies investigating tha use of behavioral techniques in the treatment of health-related problems have recently rt-)cei ved considerable emphasis. Problems such as enuresis (At~howe, 1972;Nordquist, 1971), obesity (Stuart, 19137), a.lc.oholism (Miller, 1972;Sobell and Sobell, 1973), chronic patn (Fordyce, Fowler, Lehman, and DeLateur, 1975•), and asthma (Neisworth, 1972;Renne and Creer. 1976 learning best occurs, and the variables that control behavior, might well facilitate patient recovery and make rehabilitation and patient-management programs more successful.…”
mentioning
confidence: 99%